Analysis of Epidemiological and Clinical Characteristics of COVID-19 in Northwest Mexico and the Relationship Between the Influenza Vaccine and the Survival of Infected Patients - Angulo-Zamudio, Uriel A.; Martínez-Villa, Francisco M.; Leon-Sicairos, Nidia; Flores-Villaseñor, Hector; Velazquez-Roman, Jorge; Campos-Romero, Abraham; Alcántar-Fernández, Jonathan; Urrea, Francisco; Muro-Amador, Secundino; Medina-Serrano, Julio; Martinez-Garcia, Jesus J.; Sanchez-Cuen, Jaime; et al. (Frontiers in Public Health, 2021)
The first cases of unexplained pneumonia were reported in Wuhan, China in December of 2019. Later, a novel coronavirus (SARS-CoV-2) was identified as the causal agent of pneumonia. This virus has since spread to more than 180 countries and declared a pandemic by the World Health Organization. Herein, we aimed to determine the epidemiological and clinical characteristics of symptomatic patients with coronavirus disease 2019 (COVID-19) and the relation of influenza vaccine with lower risk of COVID-19 severe infection in the state of Sinaloa. We collected demographic and clinical data of 4,040 patients with acute respiratory infections across Sinaloa state hospitals from February 28 to May 15, 2020. The prevalence of COVID-19 in among hospitalized patients with respiratory symptoms in Sinaloa was 45.2% of men were more affected than women (p<0.001), and people aged 40–49 years were the most affected. The main symptoms of COVID-19 infection were cough and fever (p<0.001), while hypertension, obesity, and type 2 diabetes were the chronic diseases associated with COVID-19 than non-COVID-19 (p<0.003). Healthcare workers were most likely to be infected compared to the rest of occupations (p<0.001). The general lethality rate was 14.1%, and males >62 years were the ones who had a higher lethality rate (p<0.001); the aforementioned chronic diseases were related to higher lethality of COVID-19 (p<0.001). Likewise, higher lethality was seen in housewives and patient retirees/pensioners compared with the rest of occupations (p<0.001). Finally, we found a relation among influenza vaccinated and lower risk of COVID-19 severe infection and mortality (p<0.001). These findings showed that healthcare workers, men >62 years with chronic diseases, and retired people were most affected. Furthermore, the influenza vaccine could decrease the severeness of COVID-19 cases.